Pediatric CNS tumors and 2021 WHO classification: what do oncologists need from pathologists? - d’Amati, Antonio; Bargiacchi, Lavinia; Rossi, Sabrina; Carai, Andrea; Bertero, Luca; Barresi, Valeria; Errico, Maria Elena; Buccoliero, Anna Maria; Asioli, Sofia; Marucci, Gianluca; Del Baldo, Giada; Mastronuzzi, Angela; et al. (Frontiers in Molecular Neuroscience, 2024)
The fifth edition of the WHO Classification of Tumors of the Central Nervous System (CNS), published in 2021, established new approaches to both CNS tumor nomenclature and grading, emphasizing the importance of integrated diagnoses and layered reports. This edition increased the role of molecular diagnostics in CNS tumor classification while still relying on other established approaches such as histology and immunohistochemistry. Moreover, it introduced new tumor types and subtypes based on novel diagnostic technologies such as DNA methylome profiling. Over the past decade, molecular techniques identified numerous key genetic alterations in CSN tumors, with important implications regarding the understanding of pathogenesis but also for prognosis and the development and application of effective molecularly targeted therapies. This review summarizes the major changes in the 2021 fifth edition classification of pediatric CNS tumors, highlighting for each entity the molecular alterations and other information that are relevant for diagnostic, prognostic, or therapeutic purposes and that patients’ and oncologists’ need from a pathology report.